Understanding the PhD as a phase in time - Araújo, Emília Rodrigues (2005)
The purpose of this article is to offer a contribution to the analysis of the time spent on researching and preparing a PhD thesis and its conceptualization as a ‘phase’. Prior research on PhD experiences used time to explain the doctorate in terms of the different lengths of time involved when comparing different disciplines and scientific areas of study (Bourdieu, 1983; Atkinson, 2000). To date, the PhD has not been considered as a genuine time experience. I intend to do so by bearing in mind the insights provided by time sociology frameworks. Thus, in this article it is assumed that respondents’ understanding of their PhD time as ‘a phase’ translates a deep experience of liminality, in which they understand themselves on the one hand as belonging simultaneously to a ‘now’ and a ‘then’ and, on the other, as being located in a linear temporal structure. In the light of the findings, it is suggested that the phase may be viewed as a key concept for theorizing the temporality of PhD experience.